KONDISI TERUMBU KARANG DAN KOMUNITAS IKAN PADA AREA PENCADANGAN KAWASAN KONSERVASI DAERAH (KKD) WATUPUTE, KABUPATEN KOLAKA UTARA - Subhan, Subhan; Wijaya, Anung; Warsandi, Ishaq; Musni, La Ode; Amrullah, Baso; Jupri, Jupri; Tenriabeng, Indri Maharani; Husein, Muhammad Ahmi (Fakultas Perikanan dan Ilmu Kelautan, 2022)
Data and information about the coral reefs' condition and fish are essential in planning a marine protected area (MPA). This study aims to provide an overview of the condition of coral reefs and the community structure of reef fish in terms of species distribution, density, and biomass in the Watupute waters – Kolaka Regency. The Point Intercept Transect is used to collect data on the condition of coral reefs and the underwater visual census for observing reef fish communities. The condition of the corals in the Watupute reserve area is generally moderate. Regarding the presence of reef fish communities, areas with higher live coral cover had higher density, number of species, size, and biomass. This area is reasonable to be recommended as a core zone in the design of MPA zonation.Keywords: coral reef, reef fish, marine protected area